Design and evaluation of mobile sensing technologies for identifying medicines by people with visual disabilities. Issue 3 (15th October 2019) - Façanha, Agebson Rocha; Carneiro Araújo, Maria Conceição; Viana, Windson; Sánchez, Jaime
Abstract : Purpose: People with visual impairments may have difficulty in identifying information, either on a bottle or package of medicine. As a result, many of them need the help of a third party to discern which medication they should take. In this perspective, this study aims to assist people with visual impairments to identify their medicine by using mobile sensing technologies. Design/methodology/approach: The authors have developed three versions of a mobile application. They use three technologies, namely, near field communication, QR code and magnetic field, for drug identification. The entire development process was based on user-centered design. And, the authors also performed an initial usability assessment of these applications with ten users who were blind. Findings: Preliminary results show user preference for the near field communication approach and reinforce some known drawbacks concerning the use of QR code by people with visual impairments. Research limitations/implications: Although the authors have evaluated these technologies with few mobile devices, they perceived that the acquired values of the magnetic field suffered distortions culminating, in some cases, in a non-identification of the medicine, or even in incorrect identification. Practical implications: Current mobile device magnet sensors are not yet robust to be used for medicine identification. Social implications: Mobile apps combined with medicine identification can contribute to the autonomy of people who are blind. Originality/value: The main contribution of this paper is to integrate and analyze distinct mobile-based sensing technologies for identifying medicines by people with visual impairments.